Hydrochar Production from Cigarette Butts and Tobacco for Dye Adsorption - Elif Hatice Gürkan; Selim Ceylan; Semra Çoruh; Sevda Esma Darama (MANAS: Journal of Engineering)
In this study, tobacco waste generated from cigarette and cigar production, as well as discarded cigarette butts resulting from cigarette use, were recycled and their use as adsorbent materials was investigated. For this purpose, both products underwent various thermal and chemical treatments and were converted into hydrochar form. Chemically activated hydrochar was used in dye removal experiments due to its high surface area and adsorbent properties. Malachite green was selected as the dye material for the project. Adsorption experiments were conducted at different initial concentrations, adsorbent doses, and contact times. In experiments on the removal of malachite green with butts and tobacco waste hydrochars, removal rates as high as 99% were obtained. As a result of adsorption experiments carried out with both hydrochars, it was observed that the adsorption fits the Langmuir isotherm model and the Pseudo-Second-Order kinetic model. Tobacco waste and discarded cigarette butts, which are cheap, readily available, and abundant, were found to be effective alternative adsorbents for malachite green removal.